Cell proliferation as assessed by expression of proliferating cell nuclear antigen or the uptake of bromodeoxyuridine in a rabbit model of leg-lengthening - Li, G; Simpson, A; Kenwright, J; Triffitt, J (1996)
Cell proliferation was assessed in an experimental system of leg-lengthening by two separate methods. The presence of proliferating cell nuclear antigen or the uptake of bromodeoxyuridine were determined immunohistochemically. Both methods indicated cell proliferation during leg-lengthening reaches a maximum at a distraction rate of 0.7 mm/day.